1997
DOI: 10.1002/qj.49712353909
|View full text |Cite
|
Sign up to set email alerts
|

The effects of convection and baroclinicity on the motion of tropical‐cyclone‐like vortices

Abstract: S u MMARYA three-layer shallow-water numerical model is used to study the motion of tropical-cyclone-like vortices in a westerly baroclinic current. The structure of the vortex and its environment are chosen to be representative of real tropical cyclones. Numerical experiments with and without convection are discussed. Several different environmental flows are considered.In calculations on a northem-hemisphere f-plane without convection, anomalies of upper-layer potential vorticity (PV) have a major influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…5). In fact, Dengler and Reeder (1997) showed that the development occurred with the O69 model even when the initial condition was neutral. This and other evidence indicates that the following statement by Emanuel (1986) is valid: ''the physics implied in this view are contained in virtually all contemporary numerical models which allow for convection and airsea heat transfer.…”
Section: Wind-induced Surface Heat Exchangementioning
confidence: 99%
“…5). In fact, Dengler and Reeder (1997) showed that the development occurred with the O69 model even when the initial condition was neutral. This and other evidence indicates that the following statement by Emanuel (1986) is valid: ''the physics implied in this view are contained in virtually all contemporary numerical models which allow for convection and airsea heat transfer.…”
Section: Wind-induced Surface Heat Exchangementioning
confidence: 99%
“…The Ooyama model attracted wide attention in the scientific community (e.g. DeMaria and Schubert, 1984, DeMaria and Pickle, 1988, Smith, 1997, Dengler and Reeder, 1997, Camp and Montgomery, 2001, Schecter and Dunkerton, 2009, Frisius and Lee, 2016 and is considered as a simple model for explaining tropical cyclone intensification.…”
Section: Intensification In Ooyama's Three-layer Modelmentioning
confidence: 99%
“…Figure 1 shows a schematic of the model configuration and defines the convective transport velocities at the interface of each layer. Assuming that momentum is conserved (an assumption not necessarily well satisfied), the convective momentum transport between layers is – have the same mathematical form as in the compressible three‐layer model of DeMaria and Pickle [1988; see also Dengler and Reeder , 1997]. As shown by these authors, the incompressible model can be interpreted in terms of compressible layers with constant potential temperature.…”
Section: Numerical Modelmentioning
confidence: 99%